2021
DOI: 10.1016/j.isci.2021.103230
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and durable uranium extraction from uranium mine tailings seepage water via a photoelectrochemical method

Abstract: Summary Current photocatalytic uranium (U) extraction methods have intrinsic obstacles, such as the recombination of charge carriers, and the deactivation of catalysts by extracted U. Here we show that, by applying a bias potential on the photocatalyst, the photoelectrochemical (PEC) method can address these limitations. We demonstrate that, owing to efficient spatial charge-carriers separation driven by the applied bias, the PEC method enables efficient and durable U extraction. The effects of mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This was attributed to the outstanding electrocatalytic performance of the A-TNTAs/Ti mesh electrode and further demonstrated that the A-TNTAs/Ti mesh electrode could significantly reduce the energy consumption of U­(VI) removal. In addition, the energy consumption of electroreduction methods using the A-TNTAs/Ti mesh electrode was much lower than that of some other U­(VI) electrochemical removal methods. , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This was attributed to the outstanding electrocatalytic performance of the A-TNTAs/Ti mesh electrode and further demonstrated that the A-TNTAs/Ti mesh electrode could significantly reduce the energy consumption of U­(VI) removal. In addition, the energy consumption of electroreduction methods using the A-TNTAs/Ti mesh electrode was much lower than that of some other U­(VI) electrochemical removal methods. , …”
Section: Resultsmentioning
confidence: 93%
“…In addition, the energy consumption of electroreduction methods using the A-TNTAs/Ti mesh electrode was much lower than that of some other U(VI) electrochemical removal methods. 22,23 One other challenge of U(VI) removal using the electrochemical method is the low removal efficiency in the presence of low concentrations of U(VI). In the previous study, the electrochemical removal efficiency of U(VI) using the Ti plate and the UO 2 /Ti electrodes significantly decreased when the initial U(VI) concentration was lower than 0.5 μM at the potential of −0.6 V. 14 However, when the A-TNTAs/Ti mesh electrode was used for the electroremoval of low-concentration U(VI) (0.15−0.5 μM), the U(VI) concentration decreased rapidly and reached the detection limit (0.0042 μM) within 30 min even at a higher reduction potential (−0.4 V) (Figure 2D).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, carbonate-containing systems exhibited >98% mass separation compared to <60% when other ions were present, e.g., Fe, Mn, Ni, and Cr [89]. Electrodeposition can also be photochemically assisted [91]. Yan et al,…”
Section: Electrodeposition/electrolysismentioning
confidence: 99%
“…Unlike seawater and groundwater, the composition of actual uranium mining wastewater is very complex. It often contains various metal salts, organic matter, and microorganisms [ 114 , 115 ]. Although some advanced photocatalysts indicated good selectivity for the photocatalytic reduction in U(VI) in the presence of multiple ions and organic compounds, the concentrations of interfering ions and organic compounds in the simulated uranium-containing wastewater used in the laboratory are at the milligram level.…”
Section: Photocatalytic U(vi) Extraction From Uranium-containing Wast...mentioning
confidence: 99%